Pengalaman komunikasi ibu tunggal di masa pandemi covid-19 - Nursanti, Siti; Dharta, Firdaus Yuni; Chaerudin, Chaerudin (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
It's not easy being a mother and a father at the same time, especially during the Covid-19 pandemic. This study aims to look at the communication experience of single mothers during the Covid-19 pandemic, this research uses a phenomenological qualitative method approach. The results of the research are that during the Covid-19 pandemic, many parents have difficulty communicating in parenting where two parents also carry out the dual function of being parents as well as being teachers for the benefit of children who also carry out learning activities at home, single mothers experience negative experiences at the same time. positive experience when carrying out the function of being both a mother and a father at the same time. Negative experiences are felt when mothers have to work for a living and become teachers for children who do learning activities at home, mothers find it difficult to communicate with children asking for educational functions usually carried out by teachers at school. A positive experience was felt by mothers during the Covid-19 pandemic when they were able to share difficulties and children could understand the condition of mothers who had to carry out the role of a single mother. This research is important to do in order to provide understanding to policy makers to consider the psychological condition of the family when they have to follow government policies to stay at home.